A Study on Employees Retention with Reference to Cholamandalam Investment and Finance Company Limited, Chennai - V. Sunitha (Mathematical Statistician and Engineering Applications, 2022)
Any organization desires to have highly skilled and potential people on rolls who can become the competitive advantage for the company. Engaging such people requires a lot of motivation in terms of work, workplace culture, supervisors and of course compensation. There are many HR practices that an organization implements to engage people because engagement leads to productivity. The only way HR department can sustain the competitive advantage is by continuously reinventing the fundamentals of people management. This study is a part of a larger study on HR Practices and its relationship with employee retention. It attempts to explore the employee’s perspective of HR practices in the organization. The objective of this study is to understand what employees think about organizational practices. In order to carry out the study Focus group discussions were conducted with employees of Cholamandalam Investment and Finance Company Limited. Analysis of responses is tracked and recorded. Themes have been drawn and discussed in detail. It emphasizes the need for organizations to adapt employee friendly practices to attract and retain the top talent. Employee Retention is a challenging concern of the organization. This study stressed on Employee Retention strategies. Employees are the assets of the organization. To retain skillful and committed employees in the organization, management should take care of employee satisfaction. Find out the reasons of employee turnover and overcome this. The purpose of this study is to prove how employee retention is essential in this day and age, and if the organizations are not awake to the situation and immediate actions are not taken to that effect, what repercussions lay ahead and how they would affect the organization and the industry. The study starts with an introduction, Company’s profile, Achievements and also the need for study, review of literature and objectives are set out for the study. Research methodology, Data analysis & Interpretation, Findings and Suggestions, and finally the Conclusion.